1997
DOI: 10.1002/(sici)1097-4628(19971017)66:3<543::aid-app15>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Dyeing behavior of polypropylene blend fiber. II. Ionic exchange mechanism of dyeing

Abstract: ABSTRACT:The dyeability of polypropylene fibres modified by two nitrogen polymeric additives containing dye sites of different basicity and accessibility was investigated using an acid dye. The thermodynamic and kinetic parameters of dyeing under infinite bath conditions were determined for four aqueous dye solutions. It is postulated that ionized molecules of acid dyes diffuse within the fiber after activation of a dye site by a suitable agent. In addition, color yield and color fastness of various dyes have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…For this purpose, basic nitrogen groups are suitable as cationic sites to interact with the anionic groups of acid dyes in an aqueous solution. Akrman et al 10 have proposed the ion exchange mechanism which is shown in Figure 13 to explain the interaction of an acid dye molecule with a polymeric dye site in an aqueous acetic acid solution.…”
Section: Dyeing Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, basic nitrogen groups are suitable as cationic sites to interact with the anionic groups of acid dyes in an aqueous solution. Akrman et al 10 have proposed the ion exchange mechanism which is shown in Figure 13 to explain the interaction of an acid dye molecule with a polymeric dye site in an aqueous acetic acid solution.…”
Section: Dyeing Behaviormentioning
confidence: 99%
“…The more basic the nitrogen, the lesser would be the required amount of the amine modifier in the PP matrix. 9 Akrman et al [9][10][11][12] have synthesized two amine polymeric additives with molecular mass of 4500 and 4300 (g/mol) and basic nitrogen content of 3.7 and 4.9%, so that after blending with polypropylene improved dye-ability with acid dyes could be encountered. They have evaluated kinetic and thermodynamic parameters of the dyeing system, ionic exchange mechanism of dyeing and effect of drawing on dye-ability of the modified polypropylene fibers.…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended to adjust the pH of the dyebath with organic acid (i.e. acetic acid) for better adsorption onto the fiber [11]. The quantity of dye lost in the discharged effluent is estimated to be around 10% for disperse dyes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies which have been proposed for modifying PP fibres include: direct modification of the constitution of PP fibres through the formation of co-polymers in order to introduce polar groups directly into the polymer chain, which can then can serve as sorption sites for the dyestuff [1,2]; the incorporation of other polymers (e.g. polyester and polymeric additives) leading to the formation of a bicomponent fibre with an increased capacity for dyestuff sorption [3][4][5][6][7][8][9][10]; the incorporation of colourless additives as dye-binding sorbents [e.g. minerals, polyhedral oligomeric silsesquioxanes (POSS) nanoparticles and clay], which also improve the dye-binding capacity [11][12][13][14]; surface modification by plasma activation or the grafting of different compounds (e.g.…”
Section: Introductionmentioning
confidence: 99%